1997
DOI: 10.1074/jbc.272.16.10538
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Nuclear Gene That Encodes the α-Subunit of the Mitochondrial F0F1-ATP Synthase Complex

Abstract: We have previously identified several positive cis-acting regulatory regions in the promoters of the bovine and human nuclear-encoded mitochondrial F 0 F 1 -ATP synthase ␣-subunit genes (ATPA). One of these cis-acting regions contains the sequence 5 -CACGTG-3 (an Ebox), to which a number of transcription factors containing a basic helix-loop-helix motif can bind. This E-box element is required for maximum activity of the ATPA promoter in HeLa cells. The present study identifies the human transcription factor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…A coordinated activation and transcription of the mitochondrial and nuclear genes for the components of the respiratory apparatus, cytochrome-c oxidase subunits and ATP synthase subunit 9, begins with the two-cell stage (42), indicating the importance of the coregulation of mitochondrial and nuclear genes in the maintenance of the normal mitochondrial function. The mammalian mitochondrial ATP synthase subunits are transcriptionally regulated by nuclear genes (3,4). Three nuclear genes, ATP5G1, ATP5G2, and ATP5G3, encoding the mitochondrial ATP synthase subunit 9, have been cloned in human Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A coordinated activation and transcription of the mitochondrial and nuclear genes for the components of the respiratory apparatus, cytochrome-c oxidase subunits and ATP synthase subunit 9, begins with the two-cell stage (42), indicating the importance of the coregulation of mitochondrial and nuclear genes in the maintenance of the normal mitochondrial function. The mammalian mitochondrial ATP synthase subunits are transcriptionally regulated by nuclear genes (3,4). Three nuclear genes, ATP5G1, ATP5G2, and ATP5G3, encoding the mitochondrial ATP synthase subunit 9, have been cloned in human Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using a crude, reconstituted, cellfree system demonstrated that recombinant USF1 could stimulate transcriptional activity from the adenoviral major late promoter and HIV promoters in an E-box dependent manner [54,55]. In co-transfection experiments, ecotopic expression of USF1 generally has been found to provide only modest stimulation of promoters containing USF binding E-box sites [55][56][57]. In other cases, ecotopic expression of USF led to significant reductions in promoter activities, perhaps due to displacement of other E-box-binding proteins with stronger activation domains [58].…”
Section: Discussionmentioning
confidence: 99%
“…USF2 isoforms dier in their N-terminal moieties, whereas they have identical b/HLH/ZIP domains (Viollet et al, 1996). In addition to the cyclin B1 gene, they have been described as positive or negative regulators of numerous genes like cd2, a1 (I) collagen, a-subunit of F 0 F 1 -ATP synthase, ribosomal RNA (Breen and Jordan, 1997;Cogswell et al, 1995;Ghosh et al, 1997;Kenny et al, 1997;Outram and Owen, 1994;Rippe et al, 1997) via the USF responsive element CACGTG. Importance of USF2 during development is illustrated by the severe loss of body weight and major alteration of brain functions of USF 7/7 mice (Sirito et al, 1998;Vallet et al, 1997Vallet et al, , 1998.…”
Section: Introduction P34mentioning
confidence: 99%